Intracellular replication of Streptococcus pneumoniae inside splenic macrophages serves as a reservoir for septicaemia - Ercoli, Giuseppe (2018)
Bacterial septicaemia is a major cause of mortality, but its pathogenesis remains poorly understood. In experimental pneumococcal murine intravenous infection, an initial reduction of bacteria in the blood is followed hours later by a fatal septicaemia. These events represent a population bottleneck driven by efficient clearance of pneumococci by splenic macrophages and neutrophils, but as we show in this study, accompanied by occasional intracellular replication of bacteria that are taken up by a subset of CD169+ splenic macrophages. In this model, proliferation of these sequestered bacteria provides a reservoir for dissemination of pneumococci into the bloodstream, as demonstrated by its prevention using an anti-CD169 monoclonal antibody treatment. Intracellular replication of pneumococci within CD169+ splenic macrophages was also observed in an ex vivo porcine spleen, where the microanatomy is comparable with humans. We also showed that macrolides, which effectively penetrate macrophages, prevented septicaemia, whereas beta-lactams, with inefficient intracellular penetration, failed to prevent dissemination to the blood. Our findings define a shift in our understanding of the pneumococcus from an exclusively extracellular pathogen to one with an intracellular phase. These findings open the door to the development of treatments that target this early, previously unrecognized intracellular phase of bacterial sepsis.